(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the results of surgical treatment for closed intertrochanteric femoral fractures using PFNA nails under fluoroscopic guidance at Ha Tinh Provincial General Hospital. Materials and methods: A descriptive case series study, combining retrospective and prospective designs, was conducted on 40 patients who underwent PFNA nailing surgery at Ha Tinh Provincial General Hospital from January 2024 to February 2026. Results: The mean age was 78.21±10.22 years, domestic accidents accounted for 82.5%, osteoporosis grades 1-2 predominated at 55%, the average operative time was 92.31± 26.36 minutes, all cases used 170mm nails, the average postoperative neck-shaft angle was 131.3± 4.6 độ, the average postoperative TAD was 23.8 ± 3.7 mm, the postoperative Harris score improved from 78.73 points at 3 months postoperatively to 86.45 points at 6 months postoperatively. Conclusion: PFNA nailing surgery under fluoroscopic guidance for the treatment of intertrochanteric femoral fractures is a safe and effective procedure.